1999
DOI: 10.1034/j.1399-3038.1999.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pre‐immunization by killed Mycobacterium bovis and vaccae on immunoglobulin E response in ovalbumin‐sensitized newborn mice

Abstract: A recently advanced hypothesis suggests that decreased exposure to T-helper (Th) 1-inducing agents causes Th2-biased differentiation in response to concomitant allergens. We therefore examined the effect of pre-immunization with killed Mycobacterium bovis and killed M. vaccae which are known to be very potent inducers of Thl immune response, on serum IgE response in ovalbumin (OVA)-sensitized newborn mice. Eighty-four newborn Balb/c mice were divided into four groups and were immunized intraperitoneally 24 h a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
0
29
0
2
Order By: Relevance
“…In addition to us, others have demonstrated a suppressive effect on various parameters of allergic inflammation in mouse models after mycobacteria pretreatment (4,5,8,9). However, except for one report from the work of Wang and Rook (7), there is no information as to the potential for these Ags in attenuating a preexisting allergic state.…”
Section: Discussionmentioning
confidence: 89%
“…In addition to us, others have demonstrated a suppressive effect on various parameters of allergic inflammation in mouse models after mycobacteria pretreatment (4,5,8,9). However, except for one report from the work of Wang and Rook (7), there is no information as to the potential for these Ags in attenuating a preexisting allergic state.…”
Section: Discussionmentioning
confidence: 89%
“…Although numerous reported epidemiological and experimental studies have demonstrated the inhibitory role of live or killed microbes or microbial components on allergic responses [18][19][20][21][22][23][24][25], the basis for this inhibition remains unclear. In particular, little experimental study has been performed on the effect and mechanism of neonatal microbial exposure on airway allergic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, preceding or concomitant activation of cells of the innate immune system with whole bacteria or bacterial-derived TLR ligands has been shown to effectively prevent allergic sensitization and/or allergic inflammation following local allergen challenge. For example, Tu¨kenmez et al observed that total IgE titers after an ovalbumin (OVA) sensitization were reduced in animals that have been preimmunized to heat-killed Mycobacterium bovis immediately after birth (Tukenmez et al, 1999). This is accompanied by attenuated histopathological changes following intratracheal allergen challenge (Ozdemir et al, 2003).…”
Section: The Role Of Microorganisms and Their Products For Allergy Prmentioning
confidence: 98%